The Greek Response to COVID-19: A True Success Story from an IBD Perspective. Issue 8 (1st June 2020) - Bamias, Giorgos; Lagou, Styliani; Gizis, Michalis; Karampekos, George; Kyriakoulis, Konstantinos G; Pontas, Christos; Mantzaris, Gerassimos J
Abstract: Background: After the first case of infection with the novel coronavirus, SARS-CoV-2, in China, an outbreak rapidly spread, finally evolving into a global pandemic. The new disease was named coronavirus disease 2019 (COVID-19) and by May 10, 2020, it has affected more than 4 million people worldwide and caused more than 270, 000 deaths. Methods: We describe the Greek experience regarding the response to COVID-19, with particular focus on 2 COVID-19 reference hospitals in the metropolitan area of Athens, the capital of Greece. Results: The first case of SARS-CoV-2 infection in Greece was reported on February 26, 2020, and prompted a decisive response from the Greek government. The primary focus was containment of virus spread, considering shortage of ICU beds. A general lockdown was implemented early on, and the national Health Care System underwent massive re-structuring. Our 2 gastrointestinal (GI) centers, which provide care for more than 1500 inflammatory bowel disease (IBD) patients, are located in hospitals that were transformed to COVID-19 reference centers. To maintain sufficient care for our patients, while also contributing to the fight against COVID-19, we undertook specific measures. These included provision of telemedicine services, electronic prescriptions and home delivery of medications, isolation of infusion units and IBD clinics in COVID-free zones of the hospitals, in addition to limiting endoscopies to emergencies only. Such practices allowed us to avoid interruption of appropriate therapies for IBD patients. In fact, within the SECURE-IBD database, there have been only 4 Greek IBD patients, to date, who have been reported as positive for SARS-CoV-2. Conclusion: Timely application of preventive measures and strict compliance to guidelines limited the spread of COVID-19 in Greece and minimally impacted our IBD community, without interfering with therapeutic management. Abstract : After the COVID-19 pandemic, Greece adopted an aggressive policy that focused on minimizing the spread of the virus and restructuring the Health Care System. Inflammatory bowel disease units efficiently modified their modes of operation to protect their patients without interrupting their treatment.